The Value of Trichoscopy in the Follow-up of Treatment Response in Patients With Androgenetic Alopecia - Seçil Yigen Iritaş; Deren özcan (Mattioli1885, 2024)
Introduction: Although trichoscopy has been used successfully in the diagnosis of androgenetic alopecia (AGA), its utility in monitoring the therapeutic outcome is not clear. Objectives: To investigate the value of trichoscopy in the follow-up of treatment response in patients with AGA. Methods: Ninety-five patients with AGA were included. Trichoscopic images were obtained on a 1 cm2 circular area in the left frontoparietal scalp pre- and post-treatment in all and in 61 patients, respectively. Two doctors evaluated those images who are less experienced (doctor A) and experienced (doctor B) in hair diseases and trichoscopy. Terminal, vellus and total hair count (THC, VHC, ToHC) and terminal to vellus hair (T/V) ratio were determined. These numerical data were also calculated by TrichoScan analysis of the same area. The agreement between trichoscopy and TrichoScan data was assessed. Results: The agreement between doctor A and TrichoScan was moderate for THC and ToHC pre-treatment and good post-treatment; poor for VHC and T/V ratio pre- and post-treatment. The agreement between doctor B and TrichoScan was excellent for THC, VHC and ToHC; good for T/V ratio pre- and post-treatment. Conclusions: Trichoscopy, when performed by a doctor experienced in hair diseases and trichoscopy, can be used as a sensitive method in monitoring the treatment response in patients with AGA which is based on the determination of THC, VHC, ToHC and T/V ratio. If it is to be performed by a less experienced doctor, it can be preferred as a sensitive follow-up method using THC and ToHC.